Lisdexamfetamine Dimesylate Effects on Binge Eating Behaviour and Obsessive–Compulsive and Impulsive Features in Adults with Binge Eating Disorder. (1st December 2015) - McElroy, Susan L.; Mitchell, James E.; Wilfley, Denise; Gasior, Maria; Ferreira‐Cornwell, M. Celeste; McKay, Michael; Wang, Jiannong; Whitaker, Timothy; Hudson, James I.
Abstract: In a published 11‐week, placebo‐controlled trial, 50 and 70 mg/d lisdexamfetamine dimesylate (LDX), but not 30 mg/d LDX, significantly reduced binge eating days (primary endpoint) in adults with binge eating disorder (BED). This report provides descriptions of LDX effects on secondary endpoints (Binge Eating Scale [BES]; Three‐Factor Eating Questionnaire [TFEQ]; Yale–Brown Obsessive Compulsive Scale modified for Binge Eating [Y‐BOCS‐BE]; and the Barratt Impulsiveness Scale, version 11 [BIS‐11]) from that study. Week 11 least squares mean treatment differences favoured all LDX doses over placebo on the BES ( p  ≤ 0.03), TFEQ Disinhibition and Hunger subscales (all p  < 0.05), and Y‐BOCS‐BE total, obsessive, and compulsive scales (all p  ≤ 0.02) and on BIS‐11 total score at 70 mg/d LDX ( p  = 0.015) and the TFEQ Cognitive Restraint subscale at 30 and 70 mg/d LDX (both p <0.05). These findings indicate that LDX decreased global binge eating severity and obsessive–compulsive and impulsive features of BED in addition to binge eating days. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.